Improved Stabilization Criteria for Neutral Time-Delay Systems. (7th September 2016) - Xiong, Lianglin; Zhang, Haiyang; Li, Yongkun; Liu, Zixin
Abstract : This paper addresses the stabilization conditions for neutral systems with mixed time delays. By constructing a novel class of Lyapunov functionals which contains an augmented Lyapunov functional, using a new class of improved Jensen's like inequalities, two improved delay-dependent stability criteria are firstly established. Next, state feedback controllers are designed according to the stability conditions in different cases. Finally, five numerical examples are provided to demonstrate the theoretical results.